3T MRI-based estimation of scalar cochlear implant electrode position - TEK, F. (Acta Otorhinolaryngol Ital, 2019)
Common techniques to evaluate intracochlear electrode position include ionised radiation by multi-slice computer tomography, digital volume tomography (MSCT, DVT) and flat panel tomography (FPT). Recent advances in the knowledge about handling MRI artefacts and the pain-free performance of MRI scans in cochlear implantees showed that estimation of the intracochlear electrode position is possible at 1.5 T with perimodiolar or midmodiolar arrays. The aim of the present study is to evaluate the assessment of the ipsilateral scalar position of a cochlear implant lateral wall electrode by MRI sequences at 3T. In a prospective study we evaluated 10 patients implanted with a diametrically bipolar implant magnet system with a lateral wall electrode in the intrascalar electrode position in an axial and coronal position and a T2 weighted sequence at 3T and a resolution of 0.8 mm. We compared the intracochlear position with routine postoperative DVT scan. In all cases, the MRT-estimated scalar position corresponded with that estimated by DVT scan. In all cases, a scala tympani position was present. While the position in the basal turn is reliably localisable, the first-turn visual assessment is difficult. Estimation of the intracochlear position of lateral wall cochlear implant electrodes by 3T MRI is possible for the basal turn. Electrode design plays a major role in visual assessment.